# How to re-arrange S = ut + 1/2at² to make T subject?

Watch
Announcements
This discussion is closed.
#1
I know it's easier by putting in the number's first...But I need this equation for writing a program..So Please cany1 tell me how to re-arrange it because I have been trying to do but couldn't do it..
0
10 years ago
#2
Make LHS=0 and use the quadratic formula
2
10 years ago
#3
...
0
10 years ago
#4
(Original post by SyedT)
s= ut + 0.5at^2

s = t^2(u/t + 0.5a)

s/t^2 = u + (0.5a)/t

t^2 = st/ (u + 0.5a)

t = s/(u+0.5a)
what's happening in that step?
If your trying to say that you've gone from
(u/t + 0.5a)
to
(u+0.5a)/t

then that's wrong.
0
10 years ago
#5
^ wrong. I don't think you can do it.
0
10 years ago
#6
(Original post by TI-84)
what's happening in that step?
If your trying to say that you've gone from
(u/t + 0.5a)
to
(u+0.5a)/t

then that's wrong.
0
10 years ago
#7
2nd order polynomial in t, use quad formula
0
10 years ago
#8
You can't do it.
0
10 years ago
#9
surely its just +-sqrt((2(s-ut))/a)) = T
0
10 years ago
#10
(Original post by shawrie777)
Make LHS=0 and use the quadratic formula
+1
0
10 years ago
#11
(Original post by cambo211)
surely its just +-sqrt((2(s-ut))/a)) = T
oh wait
just realised t in UT

stupid me

but anyway

0 = 1/2at^2 + ut - s

then T = (-u +/- sqrt(u^2 + 2as))/a
0
10 years ago
#12
which is what i did first but then you havnt got it in terms of t because you have t in both sides
0
10 years ago
#13
I made the LHS =o and completed the square and came to:

t= (-u +or- the square root of (2sa+u^2))/a

which is: -u plus or minus the square root of (2sa + u squared). Everything over a.

Is that right?
0
10 years ago
#14
(Original post by AarenHealy)
I made the LHS =o and completed the square and came to:

t= (-u +or- the square root of (2sa+u^2))/a

which is: -u plus or minus the square root of (2sa + u squared). Everything over a.

Is that right?
Yes 0
10 years ago
#15
(Original post by cambo211)
which is what i did first but then you havnt got it in terms of t because you have t in both sides
Meaning you can't rearrange 0
10 years ago
#16
(Original post by lolhenry)
Meaning you can't rearrange You can, using the formula like above.
0
10 years ago
#17
(Original post by jasbirsingh)
I know it's easier by putting in the number's first...But I need this equation for writing a program..So Please cany1 tell me how to re-arrange it because I have been trying to do but couldn't do it..
Do you HAVE to use this formula? Can't you just try another formula and work out an unknown from that, plug that unknown into a formula with T in it, then get T from that? That's what I do if I want to double check answers o.o
0
10 years ago
#18
Depends on your question, in some:

ut is usually = 0
so rearrage from S=1/2at^2?
0
10 years ago
#19
Use the quadratic formula. Don't bother rearranging it, use the formula for each individual question.
0
10 years ago
#20
s=ut + 1/2at^2

s/t=u+1/2at

2s/t=u+at

2s/t-u=at

2s-u= at^2

2s-u/a= t^2

√(2s-u)/a= t

voila.
3
X
new posts Back
to top
Latest
My Feed

### Oops, nobody has postedin the last few hours.

Why not re-start the conversation?

see more

### See more of what you like onThe Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

### Poll

Join the discussion

Yes (103)
22.49%
No (355)
77.51%